Analisis Kondisi Atmosfer pada Kejadian Hujan ES di Kota Palembang 04 November 2023 - Abdul Aziz Al Badri; Yahya Darmawan (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Seasonal transitions in Indonesia are typically accompanied by extreme weather phenomena, such as hail that occurred in the city of Palembang on November 4, 2023. The analysis of atmospheric conditions is intended to understand the dynamics of the atmosphere during the occurrence of the hailstorm phenomenon. The data used in this study include satellite imagery from Himawari-9 channels 8, 11, 13, 15, GSM data, ECMWF modelling data, and SST anomaly data. The research results indicate that anomalies in sea surface temperature and vertical convergence profiles, as well as relative humidity (RH), strengthen the potential for convective activity leading to extreme weather conditions. Based on Himawari-9 satellite imagery, the time series graph shows the lowest peak cloud temperature at around -80°C, with the Atmospheric Stability Index based on the GSM method indicating a labile atmospheric condition. Furthermore, using the RGB 24 Hour Microphysics and CCO methods, Cumulonimbus clouds were observed to begin growing at 07:20 UTC, entering the mature stage at 09:20 UTC, and starting to decay at 10:20 UTC.